Can the use of an external: internal ratio during standardised small-sided games be a detector of fatigue in professional adolescent soccer players? - Derbidge, C.; Moody, J.; Byrne, P. (ARC Journal of Research in Sports Medicine, 2019)
The aim of the investigation was to explore whether the external: internal (E:I) ratio during a standardised small-sided game (SSG) was impacted by fatigue monitoring methods in professional adolescent soccer players. Ten professional male soccer players (Mean ± SD; Age: 19.6 ± 1.4 years) data from seven standardised SSG`s (6v6+GK, 2x4 min, 40 x 35m) were analysed during the study. Total distance (TD): Heart rate exertion (HRe), PlayerLoadTM (PL): HRe and Explosive distance (ED): HRe were the E: I ratio`s analysed from the SSG`s. Morning perceived wellness score, using a customised self-report questionnaire (energy levels, sleep and muscle soreness), and Flight time: Contraction time (FT:CT), taken from a counter-movement jump (CMJ) performed prior to training, were used as markers of fatigue in the study. A Z-score of -1 was considered `fatigued`. Mixed-effect linear models revealed a significant effect for perceived wellness Z-score on TD: HRe, PL: HRe and ED: HRe, which resulted in a small increase in all E: Iratios. FT: CT Z-score resulted in a non-significant, trivial effect on TD: HRe, PL: HRe and ED: HRe. The results suggest E:I ratios are influenced by subjective fatigue, thus, E: I ratio`s may be a non-invasive tool for fatigue detection. However, caution should be taken when interpreting an increase in E: I ratio, and, therefore, the use of E: I ratio`s as a means for fatigue detection requires further investigation.